A Second Operator Is Involved in Pseudomonas aeruginosa Elastase (lasB) Activation - Anderson, Ronda M. (American Society for Microbiology, 1999)
Pseudomonas aeruginosa LasB elastase gene (lasB) transcription is controlled by the two-component quorum-sensing system of LasR, and the autoinducer, 3OC(12)-HSL (N-3-[oxododecanoyl]homoserine lactone). LasR and 3OC(12)-HSL-mediated lasB activation requires a functional operator sequence (OP1) in the lasB promoter region. Optimal activation of lasB, however, requires a second sequence of 70% identity to OP1, named OP2, located 43 bp upstream of OP1. In this study, we used sequence substitutions and insertion mutations in lasBp-lacZ fusion plasmids to explore the role of OP2 in lasB activation. Our results demonstrate that (i) OP1 and OP2 synergistically mediate lasB activation; (ii) OP2, like OP1, responds to LasR and 3OC(12)-HSL; and (iii) the putative autoinducer-binding domain of LasR is not required for synergistic activation from OP1 and OP2.